Describing Secondary Students’ Emotional Engagement in Reading Comprehension Through Small Group Discussion : A Case Study - Romi Romantika Linajaya; Nina Puspitaloka; Evi Karlina Ambarwati (Universitas Riau, 2024)
Small group discussion is a learning process by conducting small group discussions so that students have the skills to solve problems related to learning materials. As a commonly used method, small group discussion is also often used by teachers in learning English, especially in reading comprehension. The number of procedures that teachers must do when starting small group discussion learning sometimes makes teachers forget one of the steps which has an impact on students' emotional engagement during learning. While many studies focus on improving students' reading comprehension by using small group discussion, this study examines How does students' emotional engagement in learning reading comprehension through small group discussion. This study aims to describe how students' engagement in learning reading comprehension through small group discussion method. This research uses a case study design. The data was then analyzed using observation and interview. It was found that small group discussion can positively encourage students' emotional engagement in the context of reading comprehension, and can involve a positive teacher role in learning although there are drawbacks to small group discussion such as learning is too monotonous. Therefore, small group discussion seems to be recommended to be applied in reading comprehension learning.